Effect of silencing of mediator of DNA damage checkpoint protein 1 on the growth of oral squamous cell carcinoma in vitro and in vivo. (1st December 2019) - Zhang, Xiaoying; Hu, Fengling; Liu, Liuhui; Xu, Bin
Abstract : Mediator of DNA damage checkpoint protein 1 (MDC1) is involved in DNA damage repair and has been linked to tumor invasion, metastasis, and prognosis. This study investigated the effects of MDC1 in oral squamous cell carcinoma (OSCC) in vitro and in vivo . RNA interference‐mediated knockdown of MDC1 was performed in two OSCC cell lines (Tca‐8113 and KB). Real‐time PCR and western blotting were performed to determine expression of mRNA and protein, respectively, of MDC1. Cell viability was assessed using the MTT assay. Colony‐formation assays were performed by staining with 0.5% crystal violet. Cell migration and invasion were detected by Transwell assays. The role of MDC1 in OSCC was examined in vivo via injection of Tca‐8113 cells transfected with MDC1 small interfering (si)RNA or negative‐control siRNA into a mouse xenograft model of OSCC. Our results showed that MDC1 knockdown decreased cell proliferation. Inhibition of MDC1 decreased colony formation of Tca‐8113 and KB cells by 62% and 68%, respectively, and MDC1 knockdown reduced the number of migratory and invasive cells compared with the control group. Moreover, the xenograft mouse model of MDC1 knockdown showed reduced tumor growth. Our study suggests that MDC1 plays a role in tumorigenesis and might be a potential target for the treatment of patients with OSCC.